KOMUNITAS SURABAYA WOTAGEI DALAM FANDOM DAN YOUTH SUBCULTURE - Aninditya Ardhana Riswari (Universitas Andalas, 2019)
This study analyzes about Surabaya Wotagei Community whose uniqueness is different compared to other communities in Indonesia. Surabaya Wotagei Community emerged not only due to the same preference of the members but also by its uniqueness that is rarely encountered. This study uses qualitative-descriptive method through fandom and youth subculture approaches that emerged in the community. This study shows that Surabaya Wotagei Community is part of the subcultures because they exist as a community that is anti-mainstream but also stays neutral, as in not trying to fight or oppose something. Surabaya Wotagei Community offers a form of fandom with its own unique characteristics, where its members have other ways to provide support for AKB48 or JKT48 without being obsessive and possessive. On the other hand, as a community, Surabaya Wotagei Community is indeed formed by the popular youth culture which makes this community fluid and is well-known by many circles.